THE INFLUENCE OF INFLUENCER CREDIBILITY AND CONTENT CHARACTERISTICS ON PURCHASE INTENTION: THE MEDIATING ROLE OF BRAND ATTITUDE AND TRUST - Nurul Aulia, Devi (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2024)
This study explores the determinants of purchase intention among Instagram users. This research was designed using a quantitative approach. Data was collected through an online questionnaire administered to active Instagram users. Structural Equation Modeling (SEM) with AMOS software was employed to analyze the collected data. The sample size in this study is 280 respondents. The respondents are predominantly active Instagram users from West Java, with the remainder from Central Java and East Java. The results of this study emphasize the significant positive impact of influencer credibility on both brand attitude and trust. Another finding of this study is the positive influence of content characteristics on brand attitude and the negative influence of content characteristics on trust. These findings provide practical insights for social media marketers to focus more on choosing credible influencers to maximize user trust. On the other hand, marketers need to design more effective strategies to attract consumer interest and trust by considering the quality and relevance of content to enhance positive brand attitude while maintaining Instagram users' trust.